Scalovians/Schalvians – the Baltic Element in the Military Organisation of the Teutonic Order’s Dominion (Herrschaft) in Prussia - Kwiatkowski, Krzysztof (Social consequences of war, 2024)
This article deals with the military settlement of the autochthonous Scalovians created by the Teutonic Order on the north-eastern edges of Prussia. Almost two decades after the destruction of the Scalovian tribal community, in the 1290s the Teutonic Order settled a number of Scalovian warriors near Ragnit, thus creating an important military tool that significantly increased its military potential in the area. The text discusses the history of the Scalovians/ Schalvians from the end of the 13th century until the second quarter of the 15th century. It analyses the settlement changes the Scalvinians underwent, first concentrated in 1292/1293 at Schalauerburg and then after 1365/1369 at the castles of Ragnit, Splitter, Neuhaus and Tilsit. Attempts by the Teutonic Order to settle them around the country are also discussed. The issue of the Schalvians numbers and the factors of their decline in the first quarter of the 15th century is addressed next. The relationship of the Schalvian warriors to the Teutonic Order is analysed in detail, as are the forms of their permanent maintenance by the Order’s corporation and the various forms of more or less regular support by the brethren. In this context, the various military functions performed by Schalvian warriors in the military structures of the Teutonic Order’s dominion in Prussia are presented. They ranged from transporting correspondence to serving as guides, carrying out reconnaissance, guarding the areas of the Große Wildnis (‘Great Forest’) in the Prussian-Žemaitian-Lithuanian transition zone, looting (so-called struterie), supporting the crew of the Order’s castle in Ragnit and taking part in the Order’s war expeditions, where the Schalvians were either part of the Ragnit military contingent or formed a separate detachment. Although groups of Schalvian warriors were certainly not a dominant component of the military structures of the Teutonic Order’s dominion in Prussia, due to their proximity to the Neman (Nemunas) area of warfare and their excellent knowledge of the terrain and military conditions there, they significantly increased the efficiency of the Order’s military operations in the long war against Lithuania lasting from the end of the 13th to the beginning of the 15th century.